2011
DOI: 10.1007/s11033-011-1266-4
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the Nrf2 gene in non-small cell lung cancer

Abstract: Nrf2 (NFE2L2) is a transcription factor belonging to the Cap'N'Collar subfamily of basic-leucine zipper (bZIP) family of transcription factors, which plays a significant role in adaptive responses to oxidative stress. To investigate the relationship of between the mutation of Nrf2 gene and non-small cell lung cancer (NSCLC), in this study, we sequenced the Nrf2 gene from a total of 103 patients with NSCLC and corresponding blood samples. It is found that there is a discordance of Nrf2 mutations between NSCLC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 17 publications
2
20
0
3
Order By: Relevance
“…Sequencing experiments revealed that the A549 cell line harbors a mutation (glycine 333 to cysteine) in the Kelch domain and that the H460 cell line harbors a mutation (aspartic acid 236 to histidine) in the intervention region of KEAP1. No mutations in exon 2 of the NRF2 gene, the site associated with most NRF2 mutations [37], have been identified in sequencing analysis. We observed increased basal levels of NRF2 downstream target genes in the NSCLC cell lines harboring KEAP1 mutations compared with the wild-type KEAP1 NSCLC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing experiments revealed that the A549 cell line harbors a mutation (glycine 333 to cysteine) in the Kelch domain and that the H460 cell line harbors a mutation (aspartic acid 236 to histidine) in the intervention region of KEAP1. No mutations in exon 2 of the NRF2 gene, the site associated with most NRF2 mutations [37], have been identified in sequencing analysis. We observed increased basal levels of NRF2 downstream target genes in the NSCLC cell lines harboring KEAP1 mutations compared with the wild-type KEAP1 NSCLC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these two major roles, we aimed to ascertain whether GSTP1 also affects cancer prognosis in ESCC. The second reason is that GSTP1 expression is partially regulated by the Nrf2 gene, which is a transcriptional factor that is frequently upregulated in lung cancer, esophageal cancer and several other squamous cell carcinomas (29,30). In ESCC cell lines and primary samples, mutations in Nrf2 are frequently reported (31).…”
Section: Discussionmentioning
confidence: 99%
“…Somatic mutations identified in the NRF2 gene of human cancer patients are located within the 5= region of the gene encoding the N-terminal Neh2 domain (3), especially in proximity to the DLG and ETGE motifs. We surveyed the current literature (32,33) and the mutation database of the Catalogue of Somatic Mutations in Cancer at the Sanger Institute (http://www.sanger.ac.uk/cosmic) (34) and compiled the somatic mutations shown in Fig. 1.…”
Section: Somatic Mutations Encompassing Nrf2-dlg In Human Cancersmentioning
confidence: 99%